Lee Kuan Yew the grand master's insights on China, the United States, and the world - Lee, Kuan Yew 1923-; Allison, Graham T.; Blackwill, Robert D.; Wyne, Ali 1987-. (2012)
When Lee Kuan Yew speaks, presidents, prime ministers, diplomats, and CEOs listen. Lee the founding father of modern Singapore and its prime minister from 1959 to 1990 has honed his wisdom during more than fifty years on the world stage.
The future of China -- The future of the United States -- The future of U.S.-China relations -- The future of India -- The future of Islamic extremism -- The future of national economic growth -- The future of geopolitics and globalization -- The future of democracy -- How Lee Kuan Yew thinks -- Conclusion.
Keywords: Lee, Kuan Yew -- 1923- -- Interviews; Prime Ministers -- Singapore -- Interviews; World politics